The EU's productivity performance: Falling behind the curve - Fredrik Erixon; Oscar Guinea; Oscar du Roy (EconPol Forum, 2024)
The EU lags the US in productivity growth. Actions to increase innovation, investments in intangible assets, and promote market dynamism are needed to improve the EU's productivity. The EU should increase expenditure on R&D and create better incentives for private-sector R&D spending. The EU should design policies to channel savings to firm growth and boost venture capital. The EU should close its technology gap and reduce market fragmentation to support firm growth and technology adoption.
Keywords: 330